1998
DOI: 10.1111/j.1467-842x.1998.tb01444.x
|View full text |Cite
|
Sign up to set email alerts
|

Education and training in residential dementia care in Australia: needs, provision and directions

Abstract: This paper summarises existing education and training in dementia for aged care workers in Australia. The majority of aged care workers have no formal qualifications, while those with formal qualifications are mostly from a nursing background. Only half of nursing staff have attended any dementia care training. Existing training is either service based and provided in-house or by private consultants, or tertiary institution based and provided by academics and professional educators. There is considerable in-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Although the importance of knowledge of psychiatric disorders of older people is apparent, there is a dearth of literature and research in this field. There is, however, an assumption that many health professionals working with older clients have little understanding or knowledge of mental disorders of the aged (Schaie 1995) and have not had adequate training or education to care for the aged (Doyle & Ward 1998; Santo‐Novak et al. 2001; Smith et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although the importance of knowledge of psychiatric disorders of older people is apparent, there is a dearth of literature and research in this field. There is, however, an assumption that many health professionals working with older clients have little understanding or knowledge of mental disorders of the aged (Schaie 1995) and have not had adequate training or education to care for the aged (Doyle & Ward 1998; Santo‐Novak et al. 2001; Smith et al.…”
Section: Introductionmentioning
confidence: 99%
“…"""""""""""""""""""""""""""""""""""""""""""""""""""""""" 1 "Based"on"recent"returns"to"NMDSNSC"covering"information"on"11,904"workers" Globally, dementia care is provided not in hospital but in social care settings staffed in the main by non-professionals who are increasingly providing supporting people with substantial cognitive impairment (Howe & Kung, 2003;Reilly et al 2006). Caring for people with dementia within social care settings requires much more than just having Ôa kind heart and common senseÕ which has been reported as attracting most care workers (Doyle and Ward, 1998). Current working and employment conditions, with limited career pathways, may not dramatically change this perception and may be at the root of low levels of skills and lack of continuity of care.…”
Section: "" Having ôNo Qualificationsõmentioning
confidence: 99%
“…Ten years ago, in reviewing service-based and tertiary institution-based education and training in dementia care in Australia, we commented on a widely held belief that carers just needed "a kind heart and common sense" in order to work in residential care (Doyle and Ward, 1998). This attitudinal barrier to effective provision of education and training in the field has begun to recede but has not disappeared altogether.…”
Section: International Perspectives On Dementia Education Training Amentioning
confidence: 99%
“…We carried out a survey of training in dementia for staff of 98 residential care facilities in Victoria, Australia and found that 48% of 1,851 nursing home staff had attended a seminar or course on dementia (Doyle and Ward, 1998). Health professionals with registration requirements such as physicians, nurses and allied health workers rely on tertiary institutions to supply an adequate grounding in dementia in their basic training before registration, and there are variable incentives or requirements for continuing professional education in dementia.…”
Section: International Perspectives On Dementia Education Training Amentioning
confidence: 99%